People and Place The West Coast of New Zealand's South Island in history and literature - Richardson, Len (ANU Press, 2020)
"This book traces the enduring relationship between history, people and place that has shaped the character of a single region in a manner perhaps unique within the New Zealand experience. It explores the evolution of a distinctive regional literature that both shaped and was shaped by the physical and historical environment that inspired it. Looking westwards towards Australia and long shut off within New Zealand by the South Island's rugged Southern Alps, the West Coast was a land of gold, coal and timber. In the 1950s and 1960s, it nurtured a literature that embodied a sense of belonging to an Australasian world and captured the aspirations of New Zealand's emergent radical nationalism. More recent West Coast writers, observing the hollowing out of their communities, saw in miniature and in advance the growing gulf between city and regional economies aligned to an older economic order losing its relevance. Were they chronicling the last hurrah of a retreating age or crafting a literature of regional resistance? "